A positive electrode active material precursor and a method for manufacturing the same
Patent Information
- Application Number
- CN202310827751.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-06
AI Technical Summary
[0004]本发明目的是:提供一种正极活性物质前驱体及其制备方法,以解决现有技术中在制备正极材料前驱体时,共沉淀产物中容易剩余H以及SO42-而导致最终制备得到的电池容量减小的问题
[0026]本发明在制备正极活性物质前驱体时添加强碱,用于提高共沉淀产物中硫酸盐的溶解度,去除共沉淀产物中剩余的H以及SO42-,降低了产物中的S含量,解决了S导致的气体产生的问题,同时提高了正极活性物质的容量;并能减少水洗次数及用量,降低水洗成本,减少污水排放。
Smart Images

Figure CN116835557B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery cathode material precursor preparation technology, and particularly to a cathode active material precursor and its preparation method. Background Technology
[0002] Lithium-ion batteries are widely used due to their high specific energy and long cycle life. Among the cathode materials, lithium manganese iron phosphate (LiFePO4) is a novel phosphate material with two discharge plateaus at 3.4V and 4.1V, exhibiting high discharge capacity and significant advantages. x Mn y LiFePO4 is a novel phosphate-based lithium-ion battery cathode material formed by doping a certain proportion of manganese (Mn) onto lithium iron phosphate (LiFePO4). By doping with manganese, the advantageous characteristics of both iron and manganese can be effectively combined. Furthermore, manganese and iron are both located in the fourth period of the periodic table and are adjacent to each other, possessing similar ionic radii and some chemical properties; therefore, doping does not significantly affect the original structure.
[0003] The preparation routes for lithium manganese iron phosphate are similar to those for lithium iron phosphate, and the methods also include solid-phase and liquid-phase methods. Solid-phase methods include high-temperature solid-phase methods and carbothermal reduction methods, while liquid-phase methods include solvothermal methods, sol-gel methods, and co-precipitation methods. The co-precipitation method was used to prepare LiFe. x Mn y In the case of PO4, the traditional method is to use MnSO4, FeSO4 and NH4H2PO4 to co-precipitate Fe to form Fe x Mn y HPO4 is then sintered with a Li source. This method often results in residual H and SO4 in the co-precipitated product. 2- The remaining H will occupy Li sites during the sintering process, leading to a reduction in capacity. The remaining SO4... 2- Sulfur-containing gases are generated during battery charging and discharging, causing the battery to swell and bulge, and posing safety issues. Furthermore, current methods aim to remove SO4 as much as possible. 2- The remaining process requires a large amount of water to wash the product, resulting in significant wastewater discharge in industrial applications, which remains a drawback from an environmental perspective. Therefore, this invention develops a positive electrode active material precursor and its preparation method to address the problems existing in the prior art. Summary of the Invention
[0004] The objective of this invention is to provide a positive electrode active material precursor and its preparation method, thereby solving the problem that in the prior art, the co-precipitated products easily contain residual H and SO4 during the preparation of positive electrode material precursors. 2- This leads to a reduction in the capacity of the final battery.
[0005] The technical solution of this invention is: a method for preparing a positive electrode active material precursor, comprising:
[0006] S1: Prepare an aqueous solution of a metal salt, an alkaline solution, and a phosphorus source solution; wherein the aqueous solution of the metal salt includes an iron salt solution and a manganese salt solution;
[0007] S2: Add the alkaline solution into the coprecipitation reactor, maintain the temperature at 20-80℃ under an inert gas atmosphere, and stir at an average linear velocity of 0.40-6.30m / s;
[0008] S3: Add the metal salt aqueous solution and the phosphorus source solution to the coprecipitation reactor, and mix and stir with the alkaline solution for 1-72 hours to generate Mn. x Fe y NH4PO4 precipitate; the alkaline solution is used to increase the solubility of the sulfate produced in the reaction.
[0009] Preferably, in step S1, the molar concentration of the alkaline solution is 0.1–5 mol / L; the cation concentration in the metal salt aqueous solution is 0.1–5 mol / L; and the molar ratio x / y of Mn atoms to Fe atoms in the manganese salt solution and iron salt solution is 1.0–19. More preferably, the cation concentration in the metal salt aqueous solution is 1.0–2.0 mol / L; and the molar ratio x / y of Mn atoms to Fe atoms in the manganese salt solution and iron salt solution is 1.5–6.
[0010] Preferably, in step S1, the alkali used in the alkaline solution is a strong base whose concentration in a saturated aqueous solution at 25°C is not less than 0.1 mol / L and whose dissociation constant PKb is not greater than 4; and / or,
[0011] It must be a strong base that has a concentration of not less than 0.1 mol / L in a saturated aqueous solution at 25℃, a dissociation constant PKb greater than 4, and complexing properties.
[0012] Preferably, in step S1, the amount of H in the solute of the phosphorus source solution is used as a basis, and the amount of OH in the solute of the alkaline solution is... - The amount of substance is 90% to 110%; based on the PO4 content of the solute in the phosphorus source solution. - Based on the amount of substance, the amount of metal ions contained in the solute in the aqueous solution of the metal salt is 80% to 100%.
[0013] Preferably, in step S3, based on the amount of solute in the metal salt aqueous solution, the metal salt aqueous solution is added to the coprecipitation reactor at a rate of 1 to 800 mmol / h / L relative to each liter of bottom solution, and the phosphorus source solution is added to the coprecipitation reactor at a rate of 1 to 800 mmol / h / L.
[0014] Preferably, in step S3, the Mn x Fe y The NH4PO4 precipitate is mixed with the carbon source, filtered, washed with water, and dried to form a carbon-coated positive electrode active material precursor.
[0015] Preferably, the Mn x Fe y When NH4PO4 precipitate is mixed with a carbon source, the carbon source solution is added to the coprecipitation reactor at a rate of 1–100 mmol / h / L, calculated based on the amount of solute in the carbon source solution, and reacts with the Mn. x Fe y The NH4PO4 precipitate was mixed and stirred for 2 hours; wherein,
[0016] The carbon coating content accounts for 0.5 to 8 wt% of the weight of the positive electrode active material precursor.
[0017] Preferably, the alkali is selected from either NaOH or ammonia water, or a combination thereof, and is prepared to form an alkaline solution;
[0018] The manganese source is manganese sulfate;
[0019] The iron source is ferrous sulfate;
[0020] The phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.
[0021] The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium hydrogen phosphate, lithium nitrate, lithium oxalate, or lithium acetate.
[0022] The carbon source is selected from one or more of glucose, sucrose, citric acid, carbon nanotubes, graphene, graphene oxide, or acetylene black.
[0023] In preparing the positive electrode active material, the positive electrode active material precursor is mixed with a lithium source, wherein the molar ratio of the positive electrode active material precursor to the lithium source is 1:(0.98~1.08). The mixture is homogeneous by air jet milling or ball milling, and the sintering temperature is controlled at 600~850℃.
[0024] Based on a method for preparing a positive electrode active material precursor, the present invention also developed a positive electrode active material precursor obtained by the above preparation method.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] This invention involves adding a strong base during the preparation of the positive electrode active material precursor to increase the solubility of sulfate in the coprecipitate product and remove residual H and SO4 from the coprecipitate product. 2- This reduces the sulfur content in the product, solves the problem of gas generation caused by sulfur, and increases the capacity of the positive electrode active material; it also reduces the number of water washes and the amount of water used, reduces water washing costs, and reduces wastewater discharge. Attached Figure Description
[0027] The present invention will be further described below with reference to the accompanying drawings and embodiments:
[0028] Figure 1 The battery performance table is based on Examples 1-6 and the comparative examples of the present invention. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to specific embodiments:
[0030] Example 1
[0031] A precursor for a positive electrode active material is prepared by means of the following steps:
[0032] (1) Prepare a 70wt% aqueous solution of metal salt, a 10wt% NaOH solution, and a 20wt% NH4H2PO4 solution; wherein the molar concentration of NaOH solution is 2mol / L, the cation concentration in the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0033] Furthermore, NH4H2PO4 solution, as a phosphorus source solution, uses the amount of H in its solute as a benchmark, while NaOH solution uses the amount of OH in its solute as a benchmark. - The amount of substance is 90%–110%; the PO4 content of the solute in the NH4H2PO4 solution is... - Based on the amount of substance, the amount of metal ions contained in the solute in the aqueous solution of metal salt is 80% to 100%.
[0034] (2) Add 100 ml of NaOH solution to the coprecipitation reactor, maintain the temperature at 35°C, stir at an average linear velocity of 1.0 m / s, and introduce nitrogen gas to make the oxygen concentration in the solution lower than 0.5 mg / L, thereby forming a bottom liquid in the coprecipitation reactor.
[0035] (3) Based on the amount of solute in the metal salt aqueous solution, the metal salt aqueous solution is added to the coprecipitation reactor at a rate of 60 mmol / h / L relative to the bottom liquid per liter, and the phosphorus source solution is added to the coprecipitation reactor at a rate of 50 mmol / h / L. The reaction with NaOH solution produces sulfates, including Na₂SO₄ and (NH₄)₂SO₄. Since NaOH solution can increase the solubility of sulfates, after a continuous reaction for 14 hours, Mn₂ is formed. 0.6 Fe 0.4 The precipitation of NH4PO4 yields the precursor of the active substance;
[0036] (4) Add glucose to the coprecipitation reactor at a rate of 50 mmol / h / L, and react it with Mn. 0.6 Fe 0.4 The NH4PO4 precipitate was mixed and stirred for 2 hours, after which the Mn produced in the reaction was... 0.6 Fe 0.4 The NH4PO4 precursor is separated, washed with water and dried to form a carbon-coated positive electrode active material precursor; the carbon coating accounts for 1.3 wt% of the weight of the positive electrode active material precursor.
[0037] Based on the obtained precursor of the positive electrode active material, it can be mixed with a lithium source to prepare the positive electrode active material. The specific method is as follows:
[0038] The above-prepared positive electrode active material precursor was mixed with lithium carbonate at a cation molar ratio of 1:1.03 using an air jet mill or ball milling method. The mixture was then sintered at 700℃ under a nitrogen atmosphere to obtain lithium manganese iron phosphate material with the chemical formula LiMn. 0.6 Fe 0.4 PO4.
[0039] In this embodiment, NaOH solution is used as the alkaline solution added to the coprecipitation reactor. This increases the solubility of sulfate in the coprecipitate product, thereby reducing the residual H and SO4 in the coprecipitate product. 2- This reduces the sulfur (S) content in the product, solving the problem of gas generation caused by S, and simultaneously increases the capacity of the positive electrode active material. It should be noted that the following methods can also be used for selecting the alkali in the alkaline solution:
[0040] First, a strong base that satisfies the following conditions: the concentration of its saturated aqueous solution at 25℃ is not less than 0.1 mol / L, and its dissociation constant PKb is not greater than 4;
[0041] Second, it must satisfy the following conditions: the concentration of the saturated aqueous solution at 25℃ is not less than 0.1 mol / L, its dissociation constant PKb is greater than 4, and it is a strong base with complexing properties;
[0042] Alternatively, a mixture of two or more bases that meet the above conditions.
[0043] Combination Figure 1 As shown, the battery prepared using the active material of Example 1 has a tap density of 1.7 g / ml and a compaction density of 2.4 g / ml. Its specific capacity can reach 143 mAh / g, the initial coulombic efficiency reaches 92%, and the capacity retention rate can reach 98.7% after 100 cycles.
[0044] Example 2
[0045] A precursor for a positive electrode active material is prepared by means of the following steps:
[0046] (1) Prepare a 70wt% aqueous solution of metal salt, a 10wt% NaOH solution, and a 20wt% NH4H2PO4 solution; wherein the cation concentration in the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 7:3;
[0047] (2) Add 100 ml of NaOH solution to the coprecipitation reactor. The molar concentration of the NaOH solution is 2 mol / L. Keep the temperature at 35℃, stir at an average linear velocity of 1.0 m / s, and introduce nitrogen gas to make the oxygen concentration in the solution lower than 0.5 mg / L, so that a bottom liquid is formed in the coprecipitation reactor.
[0048] (3) Based on the amount of solute in the metal salt aqueous solution, the metal salt aqueous solution is added to the coprecipitation reactor at a rate of 60 mmol / h / L relative to the bottom liquid per liter, and the phosphorus source solution is added to the coprecipitation reactor at a rate of 50 mmol / h / L. The reaction with NaOH solution produces sulfates, including Na₂SO₄ and (NH₄)₂SO₄. Since NaOH solution can increase the solubility of sulfates, after a continuous reaction for 14 hours, Mn₂ is formed. 0.7 Fe 0.3 The precipitation of NH4PO4 yields the precursor of the active substance;
[0049] (4) Add glucose to the coprecipitation reactor at a rate of 50 mmol / h / L, and react it with Mn. 0.7 Fe 0.3 The NH4PO4 precipitate was mixed and stirred for 2 hours, after which the Mn produced in the reaction was... 0.7 Fe 0.3 The NH4PO4 precursor is separated, washed with water and dried to form a carbon-coated positive electrode active material precursor; the carbon coating accounts for 1.3 wt% of the weight of the positive electrode active material precursor.
[0050] Based on the obtained precursor of the positive electrode active material, it can be mixed with a lithium source to prepare the positive electrode active material. The specific method is as follows:
[0051] The above-prepared positive electrode active material precursor was mixed with lithium carbonate at a cation molar ratio of 1:1.03 using an air jet mill or ball milling method. The mixture was then sintered at 700℃ under a nitrogen atmosphere to obtain lithium manganese iron phosphate material with the chemical formula LiMn. 0.7 Fe 0.3 PO4.
[0052] The difference between Example 2 and Example 1 is that the Mn / Fe ratio is 7:3, combined with... Figure 1 As shown, the battery prepared using the active material in Example 2 has a tap density of 1.7 g / ml and a compaction density of 2.4 g / ml. Its specific capacity can reach 145 mAh / g, the initial coulombic efficiency reaches 91%, and the capacity retention rate can reach 98.2% after 100 cycles.
[0053] Example 3
[0054] A precursor for a positive electrode active material is prepared by means of the following steps:
[0055] (1) Prepare a 70wt% aqueous solution of metal salt, a 10wt% LiOH solution, and a 20wt% NH4H2PO4 solution; wherein the cation concentration in the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0056] (2) Add 100 ml of LiOH solution to the coprecipitation reactor. The molar concentration of the LiOH solution is 2 mol / L. Maintain the temperature at 35℃, stir at an average linear velocity of 1.0 m / s, and introduce nitrogen gas to make the oxygen concentration in the solution lower than 0.5 mg / L.
[0057] (3) The aqueous solution of the metal salt and the phosphorus source solution were added to the coprecipitation reactor at rates of 60 mmol / h / L and 50 mmol / h / L, respectively, to react with the LiOH solution. After a continuous reaction of 14 h, Mn was formed. 0.6 Fe 0.4 Precipitation of NH4PO4;
[0058] (4) Add glucose to the coprecipitation reactor at a rate of 50 mmol / h / L, and react it with Mn. 0.6 Fe 0.4 The NH4PO4 precipitate was mixed and stirred for 2 hours, after which the Mn produced in the reaction was... 0.6 Fe 0.4The NH4PO4 precursor is separated, washed with water and dried to form a carbon-coated positive electrode active material precursor; the carbon coating accounts for 1.3 wt% of the weight of the positive electrode active material precursor.
[0059] Based on the obtained precursor of the positive electrode active material, it can be mixed with a lithium source to prepare the positive electrode active material. The specific method is as follows:
[0060] The above-prepared positive electrode active material precursor was mixed with lithium carbonate at a cation molar ratio of 1:1.03 using an air jet mill or ball milling method. The mixture was then sintered at 700℃ under a nitrogen atmosphere to obtain lithium manganese iron phosphate material with the chemical formula LiMn. 0.6 Fe 0.4 PO4.
[0061] The difference between Example 3 and Example 1 is that the alkaline solution used is LiOH solution, combined with... Figure 1 As shown, the battery prepared using this active material has a tap density of 1.6 g / ml and a compaction density of 2.3 g / ml, a specific capacity of 142 mAh / g, an initial coulombic efficiency of 89%, and a capacity retention of 83.1% after 100 cycles. Comparison shows that the performance of the positive electrode active material prepared by adding LiOH solution during the precursor preparation process is significantly inferior to that prepared by adding NaOH solution.
[0062] Example 4
[0063] A positive electrode active material precursor is prepared in a method that differs from that in Example 1 in step (1), mainly as follows:
[0064] (1) Prepare a 70wt% aqueous solution of metal salt, a 10wt% aqueous solution of ammonia, and a 20wt% solution of NH4H2PO4; wherein the cation concentration in the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0065] In this example 4, compared to example 1, the NaOH solution was replaced with an ammonia solution; combined with Figure 1 As shown, the battery prepared using the active material in Example 4 has a tap density of 1.7 g / ml and a compaction density of 2.4 g / ml. Its specific capacity can reach 144 mAh / g, the initial coulombic efficiency reaches 92%, and the capacity retention rate can reach 98.5% after 100 cycles. The comparison shows that the use of ammonia solution and NaOH solution as alkaline solutions results in little difference in the performance of the prepared active materials.
[0066] Example 5
[0067] A positive electrode active material precursor is prepared in a method that differs from that in Example 1 in step (1), mainly as follows:
[0068] (1) Prepare a 70wt% aqueous solution of metal salt, a 0.5wt% solution of NaOH, and a 29.5wt% solution of NH4H2PO4; wherein the molar concentration of NaOH solution is 2mol / L, the cation concentration of the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0069] Combination Figure 1 As shown, the prepared battery has a tap density of 1.7 g / ml and a compaction density of 2.4 g / ml, a specific capacity of 143 mAh / g, an initial coulombic efficiency of 92%, and a capacity retention of 98.8% after 100 cycles.
[0070] Example 6
[0071] A positive electrode active material precursor is prepared in a method that differs from that in Example 1 in step (1), mainly as follows:
[0072] (1) Prepare a 70wt% aqueous solution of metal salt, a 20wt% NaOH solution, and a 10wt% NH4H2PO4 solution; wherein the molar concentration of the NaOH solution is 2mol / L, the cation concentration in the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0073] Combination Figure 1 As shown, the prepared battery has a tap density of 1.7 g / ml and a compaction density of 2.4 g / ml, a specific capacity of 143 mAh / g, an initial coulombic efficiency of 92%, and a capacity retention of 98.5% after 100 cycles.
[0074] Based on Examples 1, 5, and 6, it can be seen that when the molar concentration of NaOH solution is the same, different mass fractions have little impact on the performance of the final battery.
[0075] Comparative Example
[0076] A positive electrode active material precursor is prepared in a method that differs from that in Example 1 in step (1), mainly as follows:
[0077] (1) Prepare a 70wt% aqueous solution of metal salt, a 10wt% NaOH solution, and a 20wt% NH4H2PO4 solution; wherein the molar concentration of the NaOH solution is 1.5mol / L, the cation concentration of the aqueous solution of metal salt is 1.5mol / L, including MnSO4 and FeSO4, and the molar ratio of Mn atoms to Fe atoms is 6:4.
[0078] Combination Figure 1 As shown, the prepared battery has a tap density of 1.6 g / ml and a compaction density of 2.3 g / ml, a specific capacity of 125 mAh / g, an initial coulombic efficiency of 85%, and a capacity retention of 83.1% after 100 cycles.
[0079] Compared to Example 1, the molar concentration of NaOH solution in this comparative example is 75% of that in Example 1. Based on the performance of the prepared batteries, it can be seen that the molar concentration of NaOH solution has a significant impact on the performance of the final prepared batteries, and the performance of the batteries prepared in Example 1 is significantly better than that of the comparative example.
[0080] As a further optimization of this application, the phosphorus source may be one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the lithium source may be one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium nitrate, lithium oxalate, or lithium acetate; and the carbon source may be one or more of glucose, sucrose, citric acid, carbon nanotubes, graphene, graphene oxide, or acetylene black.
[0081] The above embodiments are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the present invention is defined by the appended claims rather than the foregoing description, and thus all changes falling within the meaning and scope of the equivalents of the claims are intended to be included within the present invention.
Claims
1. A method for preparing a positive electrode active material precursor, characterized in that, include: S1: Prepare aqueous solutions of metal salts, alkaline solutions, and phosphorus source solutions; The aqueous solution of the metal salt includes iron salt solution and manganese salt solution; The molar concentration of the alkaline solution is 0.1–5 mol / L; the cation concentration in the metal salt aqueous solution is 0.1–5 mol / L; and the molar ratio x / y of Mn atoms to Fe atoms in the manganese salt solution and iron salt solution is 1.0–19. The base used in the alkaline solution is a strong base that has a concentration of not less than 0.1 mol / L in its saturated aqueous solution at 25°C and a dissociation constant PKb not greater than 4; and / or a weak base that has a concentration of not less than 0.1 mol / L in its saturated aqueous solution at 25°C and a dissociation constant PKb greater than 4 and has complexing properties. Based on the amount of H in the solute of the phosphorus source solution, the amount of OH in the solute of the alkaline solution... - The amount of substance is 90% to 110%; based on the PO4 content of the solute in the phosphorus source solution. - Based on the amount of substance, the amount of metal ions contained in the solute in the aqueous solution of the metal salt is 80% to 100%. S2: Add the alkaline solution into the coprecipitation reactor, maintain the temperature at 20-80℃ under an inert gas atmosphere, and stir at an average linear velocity of 0.40-6.30m / s; S3: Add the metal salt aqueous solution and the phosphorus source solution to the coprecipitation reactor, and mix and stir with the alkaline solution for 1-72 hours to generate Mn. x Fe y NH4PO4 precipitation; the Mn x Fe y The NH4PO4 precipitate is mixed with the carbon source, filtered, washed with water and dried to form a carbon-coated positive electrode active material precursor. The alkaline solution is used to increase the solubility of the sulfate produced in the reaction and to remove residual H and SO4 from the coprecipitate. 2- .
2. The method for preparing a positive electrode active material precursor according to claim 1, characterized in that, In step S3, based on the amount of solute in the metal salt aqueous solution, the metal salt aqueous solution is added to the coprecipitation reactor at a rate of 1 to 800 mmol / h / L relative to each liter of bottom liquid, and the phosphorus source solution is added to the coprecipitation reactor at a rate of 1 to 800 mmol / h / L.
3. The method for preparing a positive electrode active material precursor according to claim 1, characterized in that, The Mn x Fe y When NH4PO4 precipitate is mixed with a carbon source, the carbon source solution is added to the coprecipitation reactor at a rate of 1–100 mmol / h / L, calculated based on the amount of solute in the carbon source solution, and reacts with the Mn. x Fe y The NH4PO4 precipitate was mixed and stirred for 2 hours; wherein the carbon coating amount accounted for 0.5 to 8 wt% of the weight of the positive electrode active material precursor.
4. The method for preparing a positive electrode active material precursor according to claim 1, characterized in that: The alkali is selected from either NaOH or ammonia water, or a combination thereof, and is prepared to form an alkaline solution; Manganese sulfate was selected as the manganese source. Ferrous sulfate was selected as the iron source. The phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium hydrogen phosphate, lithium nitrate, lithium oxalate, or lithium acetate. The carbon source is selected from one or more of glucose, sucrose, citric acid, carbon nanotubes, graphene, graphene oxide, or acetylene black.
5. A precursor for a positive electrode active material, characterized in that: It is prepared by the method for preparing a positive electrode active material precursor as described in any one of claims 1-4.
Citation Information
Patent Citations
Preparation method of ferromanganese ammonium phosphate for preparing lithium-ion battery anode material
CN105655584A
Preparation method of ammonium manganese ferric phosphate, lithium manganese ferric phosphate and application of lithium manganese ferric phosphate
CN115043387A